Relación dasométrica del dap y altura total con carbono almacenado en un bosque de colina baja del distrito de Mazán, Río Napo, Loreto. 2023 - Flores Rios, Nils Ericson (2024)
In the district of Mazán/Napo, Loreto, this study evaluated the dasometric relationship between DBH and total height with carbon deposited in a low hill forest of the company Green Gold Forestry S. A. (GGF GROUP). For timber purposes, information from the forest census of commercial species of the cutting plot (PC) No. 12 of the operational plan No. 1 of the logging concession contract was evaluated. According to the data, the species with the highest number of trees per hectare show Virola flexuosa (0.35 trees/ha) and Parkia multijuga (0.21 trees/ha). The distribution of the number of trees per diameter class is 2.73 trees/ha. Commercial forest species store 10.06 tC/ha of carbon in the evaluated forest; Parkia multijuga stores 0.89 tC/ha, while Virola flexuosa stores the most, with 0.91 tC/ha. The correlation coefficient for DBH and carbon stocks is excellent (r=0.791) and regular (r=0.334) for total height and carbon stocks, respectively.